1993
DOI: 10.1111/j.1464-5491.1993.tb00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Lipid Levels at Diagnosis in Type 2 Diabetic Patients

Abstract: Plasma lipid measurements were obtained at the time that 545 subjects were screened for diabetes mellitus. Both the women and men diagnosed with diabetes had significantly higher triglyceride levels (p < 0.05) and lower high-density-lipoprotein cholesterol (HDL-cholesterol) levels (p < 0.05) than those with normal glucose tolerance. Low-density-lipoprotein cholesterol (LDL-cholesterol) levels were only higher in the diabetic women (p < 0.001). Differences in lipid values were diminished somewhat with allowance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
3
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
6
3
0
Order By: Relevance
“…These changes failed to correlate with the degree of glycaemic control, urinary albumin or the duration of disease although levels of E-selectin correlated with increased levels of LDL and vWf with hypertension. In common with the findings of others, the risk factor profile of the patients differed markedly from that of the controls: there was more hypertension, hypertriglyceridaemia, smoking and increased LDL among the patients whilst HDL was lower (18)(19)(20).…”
Section: Discussionsupporting
confidence: 81%
“…These changes failed to correlate with the degree of glycaemic control, urinary albumin or the duration of disease although levels of E-selectin correlated with increased levels of LDL and vWf with hypertension. In common with the findings of others, the risk factor profile of the patients differed markedly from that of the controls: there was more hypertension, hypertriglyceridaemia, smoking and increased LDL among the patients whilst HDL was lower (18)(19)(20).…”
Section: Discussionsupporting
confidence: 81%
“…In our study the mean values of total cholesterol among male and female diabetic hypertensives and controls did not vary significantly, suggesting that diabetic dyslipidemias do not alter total cholesterol levels significantly. Similar results were observed by Sosenko et al [10] who also had lower levels of HDL-C. In our study the mean values of HDL-C among male and female diabetic hypertensives were significantly lower than that of controls.…”
Section: Discussionsupporting
confidence: 92%
“…As the age advances the occurrence of diabetes and hypertension increases, relating to this in the present study the mean age of male and female diabetic hypertensives is significantly higher than that of controls. Han et al [9] and Sosenko et al [10] also had the mean age in the same range. In our study the mean BMI of male diabetic hypertensives is 25.80 and female diabetic hypertensives is 26.36, suggesting that they are overweight and the mean waist circumference was significantly higher in male and female diabetic hypertensives than controls.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies have reported inconsistent results for plasma lipids and lipoproteins in male and female NIDDM patients (10)(11)(12)(13)(14)(15), which may be explained by small sample size and the heterogeneous nature of the diabetic population studied. The largest study was based on the National Health and Nutrition Examination Survey (NHANES) II, a population-based study in U.S., and comprised over 600 white NIDDM patients (11); only three studies (12)(13)(14) have reported data for newly diagnosed, untreated patients.…”
Section: Conclusion -Cardiovascularmentioning
confidence: 89%